Potentiality of plant production in different genotypes of Dendrocalamus strictus via ex vitro and in vitro approaches - Rani, Jyoti; Nirmal; Ramgopal; Bakshi, Meena (Indian Journal of Agroforestry, 2023)
The non-availability of suitable planting material and seeds every year, poor seed setting, short seed quiescence period, high seed sterility, low seed viability, high seed-borne diseases etc. are the major causes of low availability of quality bamboo in India. Selection and clonal propagation of elite clones in would generate enormous uniform planting material thereby, increasing productivity per unit area. Multiplication of various accessions of Dendrocalamus strictus located at FRI, Dehradun was carried out employing two approaches viz. ex vitro method by rooting culm cuttings and in vitro technique using explants in tissue culture. The ex vitro raised plants showed better growth of propagules while the in vitro approach gave a large number of propagules on short term basis. The number of propagules produced via in vitro method was more in comparison to ex vitro method. However, the shoot length, collar diameter and other parameters were found to be higher in ex vitro raised plantlets. The survival percent of macropropagated plants was seen much more than that of micropropagated plants. Large number number of leaves was seen in micropropagated plants. During, the first year of growth, micropropagated plantlets were less in height but after five years of growth both in vitro and ex vitro grown plants are presumed to reach the similar height. A comparative assessment of ex vitro and in vitro approaches with amalgamation of genotype would give impetus to the feasibility of production of planting stock of viable genotype via appropriate approach.